Investigation of cellulose acetate-ammonium salt complexes polymer electrolytes for proton battery / Siti Irma Yuana Sheikh Mohd Saaid - Sheikh Mohd Saaid, Siti Irma Yuana (2009)
CA-salt complexes and plasticized CA-salt complexes were prepared using solution cast technique. Cellulose acetate (CA) was used as polymer host, ammonium trifluoromethanesulfonate or triflate (NH4CF3SO3) as complex salt, and ethylene carbonate (EC) and propylene carbonate (PC) as plasticizers. Pristine CA has low ionic conductivity (~10-10 S cm-1). Salt was added at different concentration from 5 wt.% to 50 wt.% to form CA-salt complexes films. The complexation and interactions between polymer and salt, polymer and plasticizers, and plasticizers and salt were confirmed using Fourier Transform Infrared Spectroscopy (FTIR). It was found that NH4+ group of salt interacted with lone pair C=O of CA chain since there were band shifts at C=O (from 1733 cm-1 to 1724 cm-1) and NH4+ group (from 1630 cm-1 to 1620 cm-1). Salt provides CA chain with charge carriers (or mobile ions) and thus increases the conductivity from ~2 x 10-10 S cm-1 to 6.55 x 10-5 S cm-1 by addition of 50 wt.% salt. Plasticizers further enhanced the ionic conductivity. CA with 35 wt.% salt was chosen to be plasticized with EC and PC. From FTIR studies, EC and PC plasticizers did not show any interaction with CA but did show interaction with salt. EC has enhanced ionic conductivity of CA-salt complexes better than PC and improved the conductivity up to four orders of magnitude (6.36 x 10-8 S cm-1 to 1.75 x 10-4 S cm-1) compared to PC by just three orders (from 6.36 x 10-8 S cm-1 to 9.85 x 10-5 S cm-1) by addition of 50 wt.% plasticizers. Temperature dependence studies has shown that the conductivity increase with increasing temperature indicates 'thermally assisted hopping' mechanism. Dielectric studies show the β-relaxation or orientation of dipolar acetyl group of CA in following electric field direction. The orientation become faster and time taken to orient become less since relaxation frequency (fr) increases but relaxation time (τ) decreases as amounts of plasticizers as well as temperature increased. Two cells (Cell A and Cell B) with configuration of Zn ǁ (CA-35 wt.% salt) + 50 wt.% EC ǁ MnO2 and Zn ǁ (CA-35 wt.% salt) + 50 wt.% PC ǁ MnO2 respectively were fabricated and characterized. Cell A and Cell B stabilized the open circuit voltage (OCV) test at ~1.5 V and -1.4 V respectively. The discharge capacity of both cells were nearly the same.